Improved luminosity determination in pp collisions at [Formula: see text] using the ATLAS detector at the LHC - Aad, G. (Eur Phys J C Part Fields, 2013)
The luminosity calibration for the ATLAS detector at the LHC during pp collisions at [Formula: see text] in 2010 and 2011 is presented. Evaluation of the luminosity scale is performed using several luminosity-sensitive detectors, and comparisons are made of the long-term stability and accuracy of this calibration applied to the pp collisions at [Formula: see text]. A luminosity uncertainty of [Formula: see text] is obtained for the 47 pb(−1) of data delivered to ATLAS in 2010, and an uncertainty of [Formula: see text] is obtained for the 5.5 fb(−1) delivered in 2011.